2019
DOI: 10.1007/978-3-030-25540-4_7
|View full text |Cite
|
Sign up to set email alerts
|

Verifying Hyperliveness

Abstract: HyperLTL is an extension of linear-time temporal logic for the specification of hyperproperties, i.e., temporal properties that relate multiple computation traces. HyperLTL can express information flow policies as well as properties like symmetry in mutual exclusion algorithms or Hamming distances in error-resistant transmission protocols. Previous work on HyperLTL model checking has focussed on the alternation-free fragment of HyperLTL, where verification reduces to checking a standard trace property over an … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
96
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 63 publications
(101 citation statements)
references
References 32 publications
(71 reference statements)
0
96
0
Order By: Relevance
“…The model-checking [8,25,26], satisfiability [18,19,21], monitoring problem [1][2][3][4][22][23][24]33,34], and the first-order extension [31] of HyperLTL have been studied before. In [11], it has been shown that existential quantification in a HyperLTL formula can be reduced to strategic choice. An extensive study of the hierarchy of hyperlogics beyond HyperLTL has been initiated in [10].…”
Section: Related Workmentioning
confidence: 99%
“…The model-checking [8,25,26], satisfiability [18,19,21], monitoring problem [1][2][3][4][22][23][24]33,34], and the first-order extension [31] of HyperLTL have been studied before. In [11], it has been shown that existential quantification in a HyperLTL formula can be reduced to strategic choice. An extensive study of the hierarchy of hyperlogics beyond HyperLTL has been initiated in [10].…”
Section: Related Workmentioning
confidence: 99%
“…8 shows that dCAQE makes more progress, especially with a larger runtime where the other solvers solve very few instances after 100s. These results give rise to the hope that the scalability of more expressive synthesis approaches [3,6,8] can be improved by employing DQBF solving.…”
Section: Discussionmentioning
confidence: 94%
“…We have implemented a prototype tool that can solve the HyperQPTL realizability problem using the bounded synthesis approach [ 18 ]. More concretely, we extended the HyperLTL synthesis tool BoSy [ 7 , 9 , 12 ]. Bosy reduces the HyperLTL synthesis problem to a SMT constraint system which is then solved by [ 8 ] (for more see [ 12 ]).…”
Section: Methodsmentioning
confidence: 99%
“…Recently [12], it was shown that the synthesis problem of HyperLTL, although undecidable in general, remains decidable for many fragments, such as the ∃ * ∀ fragment. Furthermore, a bounded synthesis procedure was developed, for which a prototype implementation based on BoSy [7,9,12] showed promising results. HyperLTL is, however, intrinsically limited in expressiveness.…”
Section: Introductionmentioning
confidence: 99%